Fourès, Estieu, Perbosc : trois « félibres rouges » devant les guerres - Hervé Terral (Lengas)
Three authors stand out under the banner of the « Felibrige rouge », Fourès, Estieu, Perbosc. Their literature on wars, mainly poems, first refer to the crusade against the Albigenses but also to the Franco-Prussian wars (1870-1914). Strong supporters of the Occitan language and culture, they also intend to be « good French citizens »... and peace-lovers too. Others writers (Miremont, Vaylet) also express their views on the Great War.